Novel sulfonamide benzoquinazolinones as dual EGFR/HER2 inhibitors, apoptosis inducers and radiosensitizers - Aiten M. Soliman; Ali S. Alqahtani; Mostafa M. Ghorab (Taylor & Francis Group, 2019)
A series of sulfonamide benzoquinazolinones 5-18 was synthesized and evaluated for cytotoxic activity against MDA-MB-231 cell line. The compounds showed IC50 ranging from 0.26 to 161.49 µM. The promising compounds were evaluated for their inhibitory profile against epidermal growth factor (EGFR) and HER2 enzymes. Compound 10 showed more potent activity on both EGFR and HER2 than erlotinib (IC50 3.90 and 5.40 µM versus 6.21 and 9.42 µM). The pro-apoptotic activity of 10 was evaluated against caspase-3, Bax, B-cell lymphoma protein 2 (Bcl-2) expression levels, and cell cycle analysis. Compound 10 increased the level of caspase-3 by 10 folds, Bax level by 9 folds, decreased the level of the Bcl-2 by 0.14 and arrested the cell cycle in the G2/M phase. The radio-sensitizing activity of 10 was measured using a single dose of 8 Gy gamma radiation (IC50 decreased from 0.31 to 0.22 µM). Molecular docking was performed on EGFR and HER2 receptors.